(untitled) (International Journal of Latest Technology in Engineering Management & Applied Science, 2025)
Emergency power supply is essential in large commercial infrastructures such as shopping malls, where critical loads including lighting, pumps, and safety systems must remain operational during grid outages. Conventional diesel generators are widely used but suffer from delayed startup, noise, emissions, and high maintenance costs. To address these issues, this work proposes the design and simulation of an Emergency Battery Deployment System for terrace-level installation in malls. The proposed system employs a Battery Energy Storage System (BESS) integrated with a Battery Management System (BMS) to ensure reliable, efficient, and safe operation. A preliminary sizing of 260 kWh has been carried out to supply approximately 130 kW of critical loads for up to two hours of autonomy. The system is modeled and analyzed using ETAP software to perform load flow, outage, and fault simulations. The results demonstrate that the battery-based system offers instantaneous response, reduced operational costs, and zero local emissions, making it a sustainable alternative to diesel generators. The project also contributes to the United Nations Sustainable Development Goals (SDGs), namely Affordable and Clean Energy (SDG 7), Industry, Innovation, and Infrastructure (SDG 9), and Sustainable Cities and Communities (SDG 11)